Metoda zapobiegania oglądaniu nieodpowiednich programów telewizyjnych przez osoby małoletnie - Chodyka, Marta; Mosorov, Volodymyr (Wydawnictwa AGH, 2009)
Usually parents or guardians' supervision over children during television viewing is restricted to selecting programs by the parents, or simply establishing viewing hours for the broadcasted channels. This article consists of an overview of the available solutions, methods and security devices preventing potential viewers from viewing age-inappropriate television programs, as well as the elaborated and designed by the authors method preventing children from viewing inappropriate channels.

Nadzór rodziców lub opiekunów podczas oglądania przez dzieci programów telewizyjnych ogranicza się do selekcji programów bądź ustaleniu godzin odbioru emitowanych programów. Artykuł zawiera przegląd dostępnych rozwiązań dotyczących sposobów i urządzeń zabezpieczających przed oglądaniem programów telewizyjnych nieodpowiednich do wieku widza oraz opracowaną przez autorów metodę zapobiegania oglądania nieodpowiednich programów przez dzieci
Security method preventing potential viewers from viewing age-inappropriate TV programs
Automatyka
Keywords: parents' supervision; security method; nadzór rodziców; metoda zabezpieczająca; security device; urządzenie zabezpieczające